2021
DOI: 10.3390/s21175962
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Structural and Acoustic Parameters of the Skull Model on Transcranial Focused Ultrasound

Abstract: Transcranial focused ultrasound (tFUS) has great potential in brain imaging and therapy. However, the structural and acoustic differences of the skull will cause a large number of technical problems in the application of tFUS, such as low focus energy, focal shift, and defocusing. To have a comprehensive understanding of the skull effect on tFUS, this study investigated the effects of the structural parameters (thickness, radius of curvature, and distance from the transducer) and acoustic parameters (density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It is well known that bone yields a particularly strong effect on tFUS, with recent work showing that bone-induced attenuation can be up-to 4.70-7.06 greater than attention caused by the brain or scalp layer (Guo et al 2021). Additionally, it has been shown that bone thickness has the strongest effects on the bone-induced attenuation of tFUS (Zhang et al 2021). In this study, we observed that bone is thinnest in the temporal region (i.e., locations T3 and T4), supporting previous work using the temporal window to place the tFUS transducer to attenuate .…”
Section: Tissue Thicknesses Vary Across Age Groups Sexes and Channelssupporting
confidence: 87%
See 1 more Smart Citation
“…It is well known that bone yields a particularly strong effect on tFUS, with recent work showing that bone-induced attenuation can be up-to 4.70-7.06 greater than attention caused by the brain or scalp layer (Guo et al 2021). Additionally, it has been shown that bone thickness has the strongest effects on the bone-induced attenuation of tFUS (Zhang et al 2021). In this study, we observed that bone is thinnest in the temporal region (i.e., locations T3 and T4), supporting previous work using the temporal window to place the tFUS transducer to attenuate .…”
Section: Tissue Thicknesses Vary Across Age Groups Sexes and Channelssupporting
confidence: 87%
“…The volume of grey matter exposed to light emitted by fNIRS is inversely related with SCD, and particularly the thickness of the highly vascularized bone and soft tissue layers strongly affect fNIRS (Rolf and Andrew 2008;Cui et al 2011;Häußinger et al 2011;Takahashi et al 2011;Brigadoi and Cooper 2015). Finally, for tFUS, the thickness of tissues also plays a key role in determining the effects, and the induced sound waves are strongly influenced bone thickness (Guo et al 2021;Zhang et al 2021). Thus, it is critical to understand SCD and the tissues comprising SCD to further elucidate the effects of noninvasive brain stimulation and recording.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the first factor responsible for this variability is the type of transducer utilized to generate the ultrasonic waves ( 28 ). The second set of parameters is the skull’s impedance to LIFU penetration ( 28 , 48 , 49 ). As the thickness of animal models is not similar to human beings, it is difficult to reproduce the same preclinical effects in the clinic ( 50 ).…”
Section: Low-intensity Focused Ultrasoundmentioning
confidence: 99%
“…To simulate neural firing, researchers developed a human skull and brain phantom to test and optimize ABI detection of embedded “EEG-like” currents. Because the skull is a strong absorber and disperser of ultrasound and electrical signals (Zhang et al, 2021 ), in earlier studies, the skull cap was removed and ultrasound waves were delivered directly through the surface of the brain phantom (Qin et al, 2016 ). Barragan used a head phantom with a real human skull to demonstrate 4D ABI for mapping time-varying monopoles and dipoles at depths >60 mm with detection thresholds <0.5 mA ( Figure 4 ) (Barragan et al, 2020 ).…”
Section: Research Progressmentioning
confidence: 99%